2017
DOI: 10.1371/journal.pone.0170333
|View full text |Cite
|
Sign up to set email alerts
|

A Possible Role of the Full-Length Nascent Protein in Post-Translational Ribosome Recycling

Abstract: Each cycle of translation initiation in bacterial cell requires free 50S and 30S ribosomal subunits originating from the post-translational dissociation of 70S ribosome from the previous cycle. Literature shows stable dissociation of 70S from model post-termination complexes by the concerted action of Ribosome Recycling Factor (RRF) and Elongation Factor G (EF-G) that interact with the rRNA bridge B2a/B2b joining 50S to 30S. In such experimental models, the role of full-length nascent protein was never conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…Taken together these studies implicate, in agreement with recent studies [14], the possibility of a conserved role of unfolded protein conformation, irrespective of the identity of the protein, in influencing ribosome subunit dissociation. The unfolded protein is expected to be present at substoichiometric levels with respect to the ribosome under physiological conditions, conditions under which negligible 70S dissociation was observed in this study.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Taken together these studies implicate, in agreement with recent studies [14], the possibility of a conserved role of unfolded protein conformation, irrespective of the identity of the protein, in influencing ribosome subunit dissociation. The unfolded protein is expected to be present at substoichiometric levels with respect to the ribosome under physiological conditions, conditions under which negligible 70S dissociation was observed in this study.…”
Section: Resultssupporting
confidence: 90%
“…While the binding of tRNA to the A site might hinder access of uBCAII to crucial interaction sites residing in the A loop, the tRNA bound to the P site might interfere in the participation of nucleotides in the P loop whose mutation abolishes chaperoning activity of this RNA domain [33,34]. A recent study has also shown that while RRF, EFG, and GTP are capable of dissociating a tRNA-bound ribosome, binding of tRNA significantly suppresses unfolded-protein-mediated subunit dissociation [14]. In addition, our studies also show that ribosome subunit dissociation mediated by unfolded proteins is similarly inhibited at higher spermidine concentrations (in the presence of 7.5 mM Mg 2+ ; Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, as mentioned above, ribosome recycling from a polysome might proceed differently than from a monosome. It has also been suggested that incompletely folded full-length nascent protein newly released from a tRNA-bound ribosome might directly impact recycling ( 60 ). Clearly, further experiments will be required to resolve these points.…”
Section: Discussionmentioning
confidence: 99%